Impact of Audit Quality on Firm Performance: Evidence from Non- Financial Companies Listed in Colombo Stock Exchange - Thooyamany, A.; Balagobei, S. (Eastern University, Sri Lanka, 2025)
Auditing is a crucial component of a firm’s control system. However, in Sri Lanka, there is no standardized or mandatory code of best practices for audit quality. The purpose of this study is to investigate the impact of audit quality on the firm performance of nonfinancial companies listed on the Colombo Stock Exchange. In this study, audit fee, auditor expertise, auditor independence, and audit rotation are considered proxies for audit quality while firm performance is measured by ROA and Tobin’s Q. A sample of 94 non-financial companies listed on the Colombo Stock Exchange was selected for the study comprising 470 observations. Secondary data were collected from the annual reports of these companies for the five-year period from 2017 to 2021. Descriptive and inferential statistics were employed to analyze the data. Correlation analysis was used to examine the relationship between audit quality and firm performance while panel data regression analysis was applied to assess the impact of audit quality on firm performance. The results of the correlation analysis indicate that audit fee and auditor expertise are positively correlated with ROA whereas auditor independence and audit rotation show no relationship with firm performance as measured by ROA and Tobin’s Q. Furthermore, the panel data regression analysis reveals a significant positive impact of audit fees on firm performance while audit rotation positively influences only the ROA of listed companies in Sri Lanka. However, auditor independence and auditor expertise do not exhibit a significant impact on firm performance.This study is valuable for understanding the impact of audit quality on firm performance in the context of developing countries.
Keywords: Audit quality; Audit fee; Auditor expertise; Auditor independence; Audit rotation; Firm performance